Pomen analize dominantnih dreves za gozdnogospodarsko načrtovanje na primeru kisloljubnega bukovja z rebrenjačo - Bončina, Andrej (Gozdarski vestnik, 2022)
Knowledge on the development of dominant trees is important for forest management, especially for determining thinning regime, target tree dimensions and optimal proportions of developmental phases of forest stands. Based on data from permanent sampling plots of Slovenia Forest Service we analysed diameter of height growth of individual dominant trees of five different tree species in acidophilus beech forest type with deer fern (European beech, Norway spruce, sessile oak, Scot pine and sweet chestnut). Based on the models, the site productivity index (SPI), defined as the dominant tree height at a diameter of 45 cm, and site indices (SI) of five tree species were determined, and procedure for optimal model of developmental phases in regard to tree species composition, target tree dimension and regeneration period was developed. SPI of beech, spruce, sessile oak, Scot pine and sweet chestnut amounted to 28.4, 31.1, 25.1, 26.1 and 23.2, respectively, while site indices amounted to 27.9, 32.5, 20.9, 22.9 and 21.7. The optimal model of developmental phases depends significantly on tree species composition of forest stands and management decision on target tree dimension and regeneration regime. Individual diameter increment model of dominant beech trees showed that tree diameter, site productivity and stand heterogeneity positively influences diameter growth, while proportion of beech in a stand, stand basal area and inclination had a negative impact.
Keywords: Castanea sativa; debelinska rast; drevesa; Fagus sylvatica; gozdarstvo; Picea abies; Pinus sylvestris; Quercus petraea; rastiščni indeks; višinska rast